2022
DOI: 10.3390/automation3030023
|View full text |Cite
|
Sign up to set email alerts
|

Scientometric Analysis for Cross-Laminated Timber in the Context of Construction 4.0

Abstract: Cross-laminated timber (CLT) has been one of the principal materials in mass timber construction, and now it is possible to find mid-rise and high-rise projects around the globe. This study makes a scientometric review comparison between CLT and the impact of the fourth industrial revolution (formally known as Industry 4.0) in the construction industry, focusing on worldwide academic publications between 2006 and 2022. The analysis considers keywords, co-author, co-citation, and clustering analysis. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…A scientometric analysis of CLT and the effects of the fourth industrial revolution on the building industry was carried out by Martinez Villanueva et al [91]. Their findings indicated that the implementation of Industry 4.0 in CLT is still in its nascent stages.…”
Section: Literature Surveymentioning
confidence: 99%
“…A scientometric analysis of CLT and the effects of the fourth industrial revolution on the building industry was carried out by Martinez Villanueva et al [91]. Their findings indicated that the implementation of Industry 4.0 in CLT is still in its nascent stages.…”
Section: Literature Surveymentioning
confidence: 99%
“…In practice, Hosseini and Peer [50] verified that wood processing in sawmills should be established, using the opportunities to increase sawmill profitability and modernize plants using automation, energy efficiency, environmentally friendly production, and a line of variable products. On the other hand, relations among Industry 4.0, construction modernization and CLT production still need to be analyzed by new studies and intensified by global sectors [51]. Overall, new plants are required in regions with few or no developers, as these scenarios lead to market dominance and higher prices caused by less competition, as cited by [45].…”
Section: Future Perspectives Of the Global Industry Of Cross-laminate...mentioning
confidence: 99%
“…In line with the urgent need for sustainable civil engineering structures and controlled carbon emission from construction industry, there is a growing pressure on structural designers to use energy-efficient and eco-friendly materials. The emergence of cross-laminated timber (CLT) has a great potential to bring to an end decades-long dominance of concrete and composite floors, which significantly contribute globally to the embedded carbon footprint [1][2][3].…”
Section: Introductionmentioning
confidence: 99%